2021
DOI: 10.26552/com.c.2021.1.a54-a61
|View full text |Cite
|
Sign up to set email alerts
|

Consolidation of Cargos in the Road Transport as a Key Method to Success

Abstract: The problem of consolidation of goods for the provider of logistic services, which is a third part that delivers goods from many suppliers to one business client in time horizon was analysed in this article. Every parcel has a fixed date of reception in the source and delivery schedule in a destination. In the age of highly developed economy, time pressure and costs, outsourcing is a condition necessary to improve the functioning of enterprises. New logistic chains, networks of terminals and intermodal connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Lukasik et al . (2021) studied the benefits of consolidation of cargos in road transport, the consolidated services took the transport and handling costs into account and the findings revealed that it helped the smaller cargos to reduce costs compared to the large and medium cargos.…”
Section: Introductionmentioning
confidence: 99%
“…Lukasik et al . (2021) studied the benefits of consolidation of cargos in road transport, the consolidated services took the transport and handling costs into account and the findings revealed that it helped the smaller cargos to reduce costs compared to the large and medium cargos.…”
Section: Introductionmentioning
confidence: 99%
“…One of the fundamental problems of a modern city is to organize the transport of people and cargo so that it does not burden the inhabitants and the environment. Current urbanization processes reduce the quality of life [4]. Today, many Polish cities are crowded and overpopulated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, dredging works are nowadays an area of interest of port authorities as a necessary investment for further development [1,2]. Port dredging is a long-term and burdensome process throughout the regular operation of navigation and the normal functioning of port terminals [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%